2008
DOI: 10.1099/jmm.0.47413-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of genes encoding extracellular virulence factors among meticillin-resistant Staphylococcus aureus isolates from the University Hospital, Olomouc, Czech Republic

Abstract: A rather fast and complicated progression of an infection caused by some strains of Staphylococcus aureus could be associated with the expression and co-action of virulence factor complexes in these strains. This study screened the antibiotic susceptibility and prevalence of virulence markers in isolates of meticillin-resistant S. aureus (MRSA) obtained from patients hospitalized at the University Hospital in Olomouc, Czech Republic. A total of 100 isolates was screened for 13 genes encoding extracellular viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 46 publications
4
21
0
3
Order By: Relevance
“…The enterotoxin genes in S. aureus have been reported by many studies (7,15,19), and the prevalence of strains bearing enterotoxin genes varied in these reports. We found that 55.5% of S. aureus isolates were positive for one or more SE genes, which was higher than the rate (49.8%) of the isolates with toxigenic properties in Korea but lower than the 85.0% rate reported in the United States (6,13).…”
Section: Discussionmentioning
confidence: 95%
“…The enterotoxin genes in S. aureus have been reported by many studies (7,15,19), and the prevalence of strains bearing enterotoxin genes varied in these reports. We found that 55.5% of S. aureus isolates were positive for one or more SE genes, which was higher than the rate (49.8%) of the isolates with toxigenic properties in Korea but lower than the 85.0% rate reported in the United States (6,13).…”
Section: Discussionmentioning
confidence: 95%
“…Table 2 summarized the list of primers used for the PCR detection of ermA , ermB , ermC , msrA , and mphC genes following the protocol of Sauer et al (2008) with slight modifications. The genomic DNA was extracted using PrepMan Ultra DNA extraction kit (Applied Biosystem).…”
Section: Methodsmentioning
confidence: 99%
“…En 1932, sus descubridores (Panton y Valentine) sugirieron que era responsable de infecciones estafilocóccicas severas en humanos. Las hemolisinas también son reconocidas como potenciales factores de virulencia de S. aureus que actúan atacando la membrana celular y producen destrucción plaquetaria, destrucción lisosomal, isquemia y necrosis, por lo que son importantes en el desarrollo de patologías graves (4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionunclassified